Radioiodine Treatment of Differentiated Thyroid Cancer at CNMU, Rajshahi - Ahasan, MM; Ahmed, FU; Bodrudozza, SM; Hasan, SMK; Khanam, MN (TAJ: Journal of Teachers Association, 2009)
A retrospective study has been conducted on 19 patients who attended at CNMU, Rajshahi with differentiated thyroid cancer, treated with radioiodine for ablation of residual tissue after thyroidectomy. The patients included in this study were between 06 to 70 years of age, the mean age being about 36 years. The main objective of the study was to evaluate the response of the radioiodine therapy in patient with differentiated thyroid cancer after surgery. The incidence of papillary, follicular and mixed variety was found in approximately 69%, 26% and 5% cases respectively. Result showed that the incidence of thyroid cancer were found more, approximately 58% in the age group 21-40 years. Results also showed that papillary carcinoma involved approximately 23% in male and 77% in female. It was also found that approximately 89% patients were treated successfully by single dose of radioiodine. doi: 10.3329/taj.v16i2.3882 TAJ December 2003; Vol.16(2): 54-57